Dataset on permeability of wings from owls and non-silently flying birds - Thomas F. Geyer; Thomas Windisch; Christoph Fritzsche; Ennes Sarradj (Data in Brief, 2024)
The very soft and flow-permeable plumage is among the special adaptations of the owl that the silent flight is attributed to. Using a specially designed apparatus that provides a low-speed volume flow of air through a small sample of porous material, measurements of the air flow permeability were performed in accordance to ISO 9053 on a total of 39 prepared wing specimen from six different bird species, including three species of silently flying owls and three non-silently flying bird species. The resulting data set described in the present paper contains the static airflow resistance measured at different positions on the wing.